Efficacy of a Pre-Radiotherapy, Nurse-Led Instructional Program to Enhance the Level of Awareness of Patients Receiving Radiotherapy for First Time - Qassim, Suha Kadhim; AL-Fayyadh, Sadeq; PourGhaznein , Tayebe (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): To evaluate the effectiveness of instructional program on increase awareness level among cancer patients receiving radiation therapy for the first time. Methods: A quasi–experimental design, with a non-probability (purposive) sample of 128 patients with cancer were randomly assigned to either study group (n=64) who received a pre-radiation therapy instructional program and a control group (n=64), who only receive the routine instructions. Study instruments consist of three parts: Part I: Socio-Demographic Characteristics, Part II: Clinical Data, and Part III: Awareness Questionnaire consists of 13 items, scored by rating (2) for the correct answer and (Wilding) for the incorrect answer. Statistical package SPSS ver. (24) was used in order to analyze of the collected data. Results: This study found that the level of awareness in the study group was low (89.1%) in the pre-test phase and raised to (100%) in the post-test phase. Conclusions: There is a positive effect of the instructional program on enhancing the level of awareness about radiation therapy for cancer patients receiving radiation therapy for the first time. Recommendation: This study suggest conducting an in-person education sessions that focus on patients’ awareness about radiotherapy.